Quantitative amyloid PET in Alzheimer's disease: the AMYPAD prognostic and natural history study. Issue 5 (12th April 2020) - Lopes Alves, Isadora; Collij, Lyduine E.; Altomare, Daniele; Frisoni, Giovanni B.; Saint‐Aubert, Laure; Payoux, Pierre; Kivipelto, Miia; Jessen, Frank; Drzezga, Alexander; Leeuwis, Annebet; Wink, Alle Meije; Visser, Pieter Jelle; et al.
Abstract: Introduction: The Amyloid Imaging to Prevent Alzheimer's Disease (AMYPAD) Prognostic and Natural History Study (PNHS) aims at understanding the role of amyloid imaging in the earliest stages of Alzheimer's disease (AD). AMYPAD PNHS adds (semi‐)quantitative amyloid PET imaging to several European parent cohorts (PCs) to predict AD‐related progression as well as address methodological challenges in amyloid PET. Methods: AMYPAD PNHS is an open‐label, prospective, multi‐center, cohort study recruiting from multiple PCs. Around 2000 participants will undergo baseline amyloid positron emission tomography (PET), half of whom will be invited for a follow‐up PET 12 at least 12 months later. Results: Primary include several amyloid PET measurements (Centiloid, SUVr, BPND, R1 ), and secondary are their changes from baseline, relationship to other amyloid markers (cerebrospinal fluid and visual assessment), and predictive value of AD‐related decline. Expected Impact: Determining the role of amyloid PET for the understanding of this complex disease and potentially improving secondary prevention trials.